The efficacy of interventions in the workplace promoting exercise and a healthy diet among shift workers: A systematic review - Francielle Lopes dos Reis; Julio Cesar Ferreira Bertoloto; Ticiana da Costa Rodrigues; Sheila de Castro Cardoso Toniasso; Camila Pereira Baldin; Juliana Barros Rodrigues; Dvora Joveleviths; Maria Carlota Borba Brum (PLoS ONE, 2025)
Introduction Chronic non-communicable diseases (CNCDs) are a major public health concern, with significant impacts on quality of life and health costs. Shift work is a risk factor associated with these diseases, since it interferes with circadian rhythms and physiological processes, and can lead to circadian desynchronization and sleep deprivation. Given this scenario, the workplace is recognized by the WHO as a strategic environment for promoting health and preventing CNCDs. Objective To analyze the scientific evidence regarding the efficacy of interventions to promote healthy eating and/or physical activities among shift workers. Methods Systematic review protocol scientific databases in the field of health: MEDLINE (via PUBMED), Excerpta Medica Database (Embase), Latin American and Caribbean Literature in Health Sciences (LILACS), Web of Science and Scientific Electronic Library Online (SciELO), between January 2013 and December 2023, and was registered in the database for the study of the systematic review PROSPERO, under number: CRD42024517563. The risk of bias was analyzed according to the assessment tool, RoB 2.0 (Revised Cochrane risk-of-bias tool for randomized trials), two of the studies were evaluated using the risk of bias tool by the Non-randomized Studies – of Interventions (ROBIN I). Results The electronic search resulted in 2361 relevant articles based on the database search. After removing duplicates and articles that did not meet the inclusion criteria, 366 articles were identified. Thirteen articles were selected for full-text review, and 7 articles were included. Discussion The selected studies show that health interventions in the workplace, although with differences in the types of interventions and populations, have favorable results. Strategies aimed at nutritional support and physical activity, with the use of technologies such as motivational messages, have shown a positive impact, which is amplified when it is possible to involve workers and adapt them in the workplace. The diversity in study designs offers a broad perspective, but the variability in research methods also brings significant challenges for comparability, which justifies the decision not to carry out a meta-analysis. In addition, most studies focus on short-term interventions and outcomes, which may not adequately reflect the long-term health benefits or risks associated with shift work. Conclusion The diversity of interventions suggests that there is no single solution to promote health at the workplace. The strategies can be adapted to the specific needs and contexts of the workers and working environments. The adherence of the managers is a way of reinforcing the importance of preventative actions and allows a better adaptation of the organizational context to these activities. The lack of long-term follow-up and continued adherence are challenges that need more investment and organizational policies to ensure the effectiveness of the actions.